PENGARUH CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2017) - Agustin Dwi Haryanti (Jurnal Akademi Akuntansi, 2019)
This study aims to examine and analyze the effect of corporate governance to tax avoidance. Corporate governance is projected with two independent variables, there are proportion of independent commissioners and the number of audit committees. An independent commissioner is a part that is not affiliated with the shareholders, the Board of Directors, and/or the Board of Commissioners. Independent Commissioner is not a director of the company. The Audit Committee has the task of assisting the Board of Commissioners to improve the quality of financial reports and increase the effectiveness of internal and external audits. The Chairman of the Audit Committee is an Independent Commissioner. Tax avoidance as the dependent variable is projected with effective tax rate. Descriptive statistical research uses secondary data in the form of annual report 2017 (audited) manufacturing companies using SPSS. The proportion of Independent Commissioners has an effect on the Effective Tax Rate which has a coefficient of determination of 0,7%. The Audit Committee has an effect on the Effective Tax Rate which has a determination coefficient of 2,1%. The study concluded that independent commissioners and the number of audit committees had an effect on the effective tax rate, although not too significant. This shows that the role of the Independent Commissioner is less than optimal, and the functions of the Audit Committee cannot operate properly.